Sport-related concussion knowledge and attitudes of staff working in English elite women`s football: a survey-based study - Shafik, A.; Lota, K. S.; Mifsud, D.; Bennett, P.; Rosenbloom, C.; Kryger, K. O.; Carmody, S.; Power, J. (Science and Medicine in Football, 2025)
Background: Sport-related concussion (SRC) remains an injury of concern in sport, including football(soccer). There has been little investigation into SRC knowledge and attitudes of support staff working in the professional setting. Methods: An amended version of the Rosenbaum Concussion Knowledge and Attitudes Survey(RoCKAS) was distributed online to coaching staff, and medical and performance staff, working at clubs in the English Football Association Women`s SuperLeague (WSL) and Championship. Completion of the survey generated two scores: concussion knowledge index (CKI) and concussion attitudes index (CAI). Results: Sixty-three completed surveys were returned. Eighteen respondents were coaching staff, and 45 were medical and performance staff. The median CKI in medical and performance staff was significantly greater than in coaching staff. There was no significant difference in CAIbetween coaching staff and medical and performance staff. There was no correlation between CKI and CAI across all staff. Conclusion: Medical and performance staff working in elite women`s football have greater knowledge of SRC than coaching staff. However, this does not always translate into safe behaviours on the field. Education should continue to be mandated across the professional game amongst support staff in order to maximise player welfare and enhance injury outcomes, whilst also reinforcing present SRC guidance.